2006
DOI: 10.1177/0011128704267476
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Community Violence and Childhood Delinquency

Abstract: Community-level factors such as disadvantage, disorder, and disorganization have been linked to a variety of antisocial and illicit activities. Although crime and deviance tend to concentrate in areas with these characteristics, not all residents of disorganized neighborhoods participate in proscribed activities. This study examines the relationship between exposure to community violence and involvement in assaultive behavior and weapon carrying among a sample of at-risk youth. Findings demonstrate that contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 36 publications
2
62
0
1
Order By: Relevance
“…Although neighborhoods are typically conceptualized from a macro-level perspective, some criminologists have offered compelling rationales that there is substantial variation across individuals in perceptions of their social environment (Caspi, 1993;Wikström & Treiber, 2007). This study, along with others (Hill et al, 1999;Lambert et al, 2004;Patchin et al, 2006), indicates that individual perceptions of neighborhoods do in fact influence the likelihood of offending. These findings suggest that aggregated (i.e., mean level) indicators of neighborhoods may mask more nuanced relationships of how neighborhoods influence offending.…”
Section: Discussionmentioning
confidence: 68%
“…Although neighborhoods are typically conceptualized from a macro-level perspective, some criminologists have offered compelling rationales that there is substantial variation across individuals in perceptions of their social environment (Caspi, 1993;Wikström & Treiber, 2007). This study, along with others (Hill et al, 1999;Lambert et al, 2004;Patchin et al, 2006), indicates that individual perceptions of neighborhoods do in fact influence the likelihood of offending. These findings suggest that aggregated (i.e., mean level) indicators of neighborhoods may mask more nuanced relationships of how neighborhoods influence offending.…”
Section: Discussionmentioning
confidence: 68%
“…Drug use has been shown to increase with age and exposure to peer and neighborhood factors also likely increases with age. 23 Given past research indicating differential effects of neighborhood on problem behaviors by gender, [14][15][16] exposure-outcome relationships were modeled separately for males and females (participant-reported gender). Self-reported race and maternal education were used to describe the population but not treated as confounders, given a lack of direct causal association with the outcome and likely collinearity with explanatory variables.…”
Section: Methodsmentioning
confidence: 99%
“…Another multi-level study using data from the National Educational Longitudinal Study by Hoffmann (2006) revealed that the percentage of female-headed families had a positive effect on individual delinquency. Among other individual-and mixed-level studies, a few have demonstrated positive effects of single parenthood on delinquency (Anderson, 2002;Bernburg and Thorlindsson, 2007;Dunifon and Kowaleski-Jones, 2002;Hay et al, 2006;Haynie et al, 2006;Perrone et al, 2004;Rodgers and Rose, 2002;Weijters et al, 2007), whereas others found the effects to be marginal or nonsignificant (Ingram et al, 2007;Katz, 2000;Patchin et al, 2006;Rankin and Quane, 2002;Regnerus, 2003).…”
Section: Review Of Research Studiesmentioning
confidence: 99%